Document titled 'Military operations 1917-1921 - information from M.S.P. files' - Military Service (1916-1923) Pension Board (1937)
Carbon typescript list of Divisions and Brigades and the county area they included.
Keywords: Irish Republican Army; Irish Volunteers; Ireland -- History -- War of Independence, 1919-1921; Ireland -- History -- 1910-1921; Ireland -- History -- 1922-